New additions to the myxobiota of Peru - Rojas Alvarado, Carlos Alonso (2011)
Recent efforts to study myxomycetes in many areas of the world have resulted in a considerable increase in the number and quality of regional species lists, especially during the last decade. However, in South America certain countries such as Peru continue to be highly understudied with respect to this group of organisms. During a series of surveys carried out in 2007 in several different areas of Peru, 49 species of myxomycetes not previously known for this country were recorded. Basic ecological information was also collected and analyzed in the context of available data on myxomycetes for the Neotropics. With the new species reported herein, the myxobiota of Peru is increased to 80 species, which is still a low number when the natural and biogeographical characteristics of Peruvian landscapes are considered.